Communicative Cultural Dakwah of Abdurrahman Wahid in Pluralistic Society - Syabibi, Muhammad Ridho; Karim, Abdul; Kulkarni, Shirin; Sahil, Azharuddin (Universitas Islam Negeri Madura, 2021)
The purpose of this study was to examine the background of the life and thoughts of Abdurrahman Wahid or known as Gus Dur in the context of dakwah and communication using a social hermeneutic approach. Critical thinking, history, context of religious issues and Gus Dur’s missionary movement are identified in his various works and socio-religious roles. This type of research is qualitative factual history and literature study, namely research that uses library materials as the main data source. The research approach used is a hermeneutic and historical-sociological approach. The research methods are historical descriptive methods and biographical reconstructions. The data collected from the two approaches were analyzed by descriptive analysis presented inductively based on the framework of Habermas’ communication theory. The results of this study shows: Gus Dur emphasized that Islam is as social ethics based on historical-critical, and normative-theological, that reality epistemologically is plural, and the dialogue is necessary.